Editorial - Arif Hossain (Bangladesh Journal of Bioethics, 2022)
We are living in a corona pandemic environment. Despite this, we are going ahead. Let us hope for a coming future. The current issue of BJB is designed by the articles on the ethical issues in the environment. Following is a brief sum-up of each paper: